Novel processing technique to produce three dimensional polyvinyl alcohol/maghemite nanofiber scaffold suitable for hard tissues - Ngadiman, N.; Yusof, N.; Idris, A.; Fallahiarezoudar, E.; Kurniawan, Denni (2018)
Fabrication of three dimensional (3D) tissue engineering scaffolds, particularly for hard tissues remains a challenge. Electrospinning has been used to fabricate scaffolds made from polymeric materials which are suitable for hard tissues. The electrospun scaffolds also have structural arrangement that mimics the natural extracellular matrix. However, electrospinning has a limitation in terms of scaffold layer thickness that it can fabricate. Combining electrospinning with other processes is the way forward, and in this proposed technique, the basic shape of the scaffold is obtained by a fused deposition modelling (FDM) three dimensional (3D) printing machine using the partially hydrolysed polyvinyl alcohol (PVA) as the filament material. The 3D printed PVA becomes a template to be placed inside a mould which is then filled with the fully hydrolysed PVA/maghemite (Î³-Fe 2 O 3 ) solution. After the content in the mould solidified, the mould is opened and the content is freeze dried and immersed in water to dissolve the template. The 3D structure made of PVA/maghemite is then layered by electrospun PVA/maghemite fibers, resulting in 3D tissue engineering scaffold made from PVA/maghemite. The morphology and mechanical properties (strength and stiffness) were analysed and in vitro tests by degradation test and cell penetration were also performed. It was revealed that internally, the 3D scaffold has milli- and microporous structures whilst externally; it has a nanoporous structure as a result of the electrospun layer. The 3D scaffold has a compressive strength of 78.7 Â± 0.6 MPa and a Young's modulus of 1.43 Â± 0.82 GPa, which are within the expected range for hard tissue engineering scaffolds. Initial biocompatibility tests on cell penetration revealed that the scaffold can support growth of human fibroblast cells. Overall, the proposed processing technique which combines 3D printing process, thermal inversion phase separation (TIPS) method and electrospinning process has the potential for producing hard tissue engineering 3D scaffolds.